Corrigendum to “Unravelling inulin molecules in food sources using a matrix-assisted laser desorption/ionization magnetic resonance mass spectrometry (MALDI-MRMS) pipeline” [Food Res. Int. 184 (2024) 114276] - Sung-Tong Chin; Berin A. Boughton; Melvin C.L. Gay; Alyce C. Russell; Yimin Wang; Vimalnath Nambiar; Mark P. McHenry; Elaine Holmes; Jeremy K. Nicholson; Ruey Leng Loo (Food Research International, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Innovative In Vitro-In Silico Platform for Dose–Response Modeling in Canine Bladder Cancer: A 3D Organoid- and Mathematics-Based Approach - Mackenzie Long; Yvonne Peng; Saumya Gade; Hannah Nicholson; Michael Catucci; Christopher Zdyrski; Aleksandra Pawlak; Megan Corbett; Corey Saba; Travis Laver; Emily Rawlings; Maria Orbay-Cerrato; et al. (The AAPS Journal, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Autonomous observations enhance our ability to observe the biological carbon pump across diverse carbon export regimes - Shawnee Traylor; David P. Nicholson; Samantha J. Clevenger; Ken O. Buesseler; Eric D'Asaro; Craig M. Lee (Limnology and Oceanography, 2025)
The expansion of autonomous observation platforms offers vast opportunities for analyzing ocean ecosystems and their role in carbon export. As part of the EXport Processes in the Ocean from RemoTe Sensing campaign, we autonomously measured the productivity regimes in two contrasting end‐member ecosystem states. The first campaign occurred in the subpolar North Pacific near Ocean Station Papa (Site 1), characterized by iron limitation and a highly regenerative regime. The second captured a springtime bloom in the North Atlantic (Site 2), which typically drives efficient export of productivity. Using a combination of floats and gliders carrying biogeochemical sensors, we quantified gross primary productivity, net community production, and organic carbon export potential ( f C org ) to assess biological carbon pump strength. Site 2 demonstrated higher cruise‐period productivity, with roughly 5× the gross primary productivity and 13× the euphotic zone net community production seen at Site 1. Greater export efficiency at Site 2 was reflected in numerous indices, such as the ratio of new production to net primary productivity ( ef ‐ratio; Site 1: 0.33; Site 2: 0.73), the ratio of sinking particulate organic carbon to net primary productivity ( ez ‐ratio; Site 1: 0.24; Site 2: 0.69), and mean daily f C org (Site 1: 3.4 ± 0.7; Site 2: 20.3 ± 2.3 mmol C m −2 d −1 ). Together with particulate organic carbon flux derived from thorium‐234 measurements, we infer that observed low net community production was almost entirely routed to sinking particulate organic carbon at Site 1, while the much higher net community production at Site 2 resulted in near‐equal proportions routed to dissolved organic carbon production and sinking particulate organic carbon.

Data space inversion for efficient predictions and uncertainty quantification for geothermal models - Alex de Beer; Andrew Power; Daniel Wong; Ken Dekkers; Michael Gravatt; Elvar K. Bjarkason; John P. O’Sullivan; Michael J. O’Sullivan; Oliver J. Maclaren; Ruanui Nicholson (Computers & Geosciences, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Oxygen optodes on oceanographic moorings: recommendations for deployment and in situ calibration - Una Kim Miller; Kristen E. Fogaren; Dariia Atamanchuk; Clare Johnson; Jannes Koelling; Isabela Le Bras; Margaret Lindeman; Hiroki Nagao; David P. Nicholson; Hilary Palevsky; Ellen Park; Meg Yoder; et al. (Frontiers in Marine Science, 2024)
Increasing interest in the deployment of optical oxygen sensors, or optodes, on oceanographic moorings reflects the value of dissolved oxygen (DO) measurements in studies of physical and biogeochemical processes. Optodes are well-suited for moored applications but require careful, multi-step calibrations in the field to ensure data accuracy. Without a standardized set of protocols, this can be an obstacle for science teams lacking expertise in optode data processing and calibration. Here, we provide a set of recommendations for the deployment and in situ calibration of data from moored optodes, developed from our experience working with a set of 60 optodes deployed as part of the Gases in the Overturning and Horizontal circulation of the Subpolar North Atlantic Program (GOHSNAP). In particular, we detail the correction of drift in moored optodes, which occurs in two forms: (i) an irreversible, time-dependent drift that occurs during both optode storage and deployment and (ii) a reversible and pressure-and-time-dependent drift that is detectable in some optodes deployed at depths greater than 1,000 m. The latter is virtually unidentified in the literature yet appears to cause a low-bias in measured DO on the order of 1 to 3 µ mol kg −1 per 1,000 m of depth, appearing as an exponential decay over the first days to months of deployment. Comparisons of our calibrated DO time series against serendipitous mid-deployment conductivity-temperature-depth (CTD)-DO profiles, as well as biogeochemical (BGC)-ARGO float profiles, suggest the protocols described here yield an accuracy in optode-DO of ∼1%, or approximately 2.5 to 3 µ mol kg −1 . We intend this paper to serve as both documentation of the current best practices in the deployment of moored optodes as well as a guide for science teams seeking to collect high-quality moored oxygen data, regardless of expertise.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Unravelling inulin molecules in food sources using a matrix-assisted laser desorption/ionization magnetic resonance mass spectrometry (MALDI-MRMS) pipeline - Sung-Tong Chin; Berin A. Boughton; Melvin C.L. Gay; Alyce C. Russell; Yimin Wang; Vimalnath Nambiar; Mark P. McHenry; Elaine Holmes; Jeremy K. Nicholson; Ruey Leng Loo (Food Research International, 2024)

Spatially explicit ecosystem accounts for coastal wetland restoration - Micheli D. P. Costa; Melissa Wartman; Peter I. Macreadie; Lawrance W. Ferns; Rhiannon L. Holden; Daniel Ierodiaconou; Kimberley J. MacDonald; Tessa K. Mazor; Rebecca Morris; Emily Nicholson; Andrew Pomeroy; Elisa A. Zavadil; et al. (Ecosystem Services, 2024)

Interannual teleconnections in the Sahara temperatures associated with the North Atlantic Oscillation (NAO) during boreal winter - Liming Zhou; Wenjian Hua; Sharon E. Nicholson; Joseph P. Clark (Climate Dynamics, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Effect of light spectra on cereal fungal pathogens, a review - M. Cerón-Bustamante; E. Balducci; G. Beccari; P. Nicholson; L. Covarelli; P. Benincasa (Fungal Biology Reviews, 2023)

Mapping connectivity and conservation opportunity on agricultural lands across the conterminous United States - Justin P. Suraci; Caitlin E. Littlefield; Charlie C. Nicholson; Mitchell C. Hunter; Ann Sorensen; Brett G. Dickson (Biological Conservation, 2023)

Spatial and temporal variations in atmospheric gas flux from the Hudson River: the estuarine gas exchange maximum - Malcolm E. Scully; Anna P. M. Michel; David P. Nicholson; Shawnee Traylor (Limnology and Oceanography, 2022)
A unique combination of data collected from fixed instruments, spatial surveys, and a long‐term observing network in the Hudson River demonstrate the importance of spatial and temporal variations in atmospheric gas flux. The atmospheric exchanges of oxygen (O 2 ) and carbon dioxide (CO 2 ) exhibit variability at a range of time scales including pronounced modulation driven by spring‐neap variations in stratification and mixing. During weak neap tides, bottom waters become enriched in pCO 2 and depleted in dissolved oxygen because strong stratification limits vertical mixing and isolates sub‐pycnocline water from atmospheric exchange. Estuarine circulation also is enhanced during neap tides so that bottom waters, and their associated dissolved gases, are transported up‐estuary. Strong mixing during spring tides effectively ventilates bottom waters resulting in enhanced CO 2 evasion and O 2 invasion. The spring‐neap modulation in the estuarine portion of the Hudson River is enhanced because fortnightly variations in mixing have a strong influence on phytoplankton dynamics, allowing strong blooms to occur during weak neap tides. During blooms, periods of CO 2 invasion and O 2 evasion occur over much of the lower stratified estuary. The along‐estuary distribution of stratification, which decreases up‐estuary, favors enhanced gas exchange near the limit of salt, where vertical stratification is absent. This region, which we call the estuarine gas exchange maximum (EGM), results from the convergence in bottom transport and is analogous to the estuarine turbidity maximum (ETM). Much like the ETM, the EGM is likely to be a common feature in many partially mixed and stratified estuarine systems.

Designing and managing biodiverse streetscapes: key lessons from the City of Melbourne - Hui-Anne Tan; Lee Harrison; Jeff Nelson; Maggie Lokic; John P. Rayner; Caragh G. Threlfall; Jessica Baumann; Adrian Marshall; Mark Callow; Jessica Peeler; Rebecca Korossy-Horwood; Chris Nicholson; et al. (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Finding Oxford’s medieval Jewry using organic residue analysis, faunal records and historical documents - J. Dunne; E. Biddulph; P. Manix; T. Gillard; H. Whelton; S. Teague; C. Champness; L. G. Broderick; R. Nicholson; P. Blinkhorn; E. Craig-Atkins; B. Jervis; et al. (Archaeological and Anthropological Sciences, 2021)
Food is often one of the most distinctive expressions of social, religious, cultural or ethnic groups. However, the archaeological identification of specific religious dietary practices, including the Jewish tradition of keeping kosher , associated with ritual food practices and taboos, is very rare. This is arguably one of the oldest known diets across the world and, for an observant Jew, maintaining dietary laws (known as Kashruth) is a fundamental part of everyday life. Recent excavations in the early medieval Oxford Jewish quarter yielded a remarkable assemblage of animal bones, marked by a complete absence of pig specimens and a dominance of kosher (permitted) birds, domestic fowl and goose. To our knowledge, this is the first identification of a Jewish dietary signature in British zooarchaeology, which contrasted markedly with the previous Saxon phase where pig bones were present in quantity and bird bones were barely seen. Lipid residue analysis of pottery from St Aldates showed that vessels from the possible Jewish houses were solely used to process ruminant carcass products, with an avoidance of pig product processing, correlating well with the faunal data. In contrast, lipid analysis of pottery from comparative assemblages from the previous Saxon phase at the site and a contemporaneous site in the city, The Queen’s College, shows that the majority of these vessels appear to have been used to process mixtures of both ruminant and non-ruminant (pig) products. Here, the combination of organic residue analysis, site excavation and animal and fish bone evidence was consistent with the presence of Jewish houses in eleventh- and twelfth-century St Aldates, Oxford, hitherto only suspected through documentary information. This is the first identification of specific religious dietary practices using lipid residue analysis, verifying that, at least 800 years ago, medieval Jewish Oxford communities practised dietary laws known as Kashruth.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Ocean Time Series Observations of Changing Marine Ecosystems: An Era of Integration, Synthesis, and Societal Applications - Heather M. Benway; Laura Lorenzoni; Angelicque E. White; Björn Fiedler; Naomi M. Levine; David P. Nicholson; Michael D. DeGrandpre; Heidi M. Sosik; Matthew J. Church; Todd D. O’Brien; Margaret Leinen; Robert A. Weller; et al. (Frontiers in Marine Science, 2019)

Simultaneous‐count models to estimate abundance from counts of unmarked individuals with imperfect detection - Gerard Edward Ryan; Emily Nicholson; Jonathan C. Eames; Thomas N. E. Gray; Robin Loveridge; Simon P. Mahood; Phearun Sum; Michael A. McCarthy (Conservation Biology, 2019)
We developed a method to estimate population abundance from simultaneous counts of unmarked individuals over multiple sites. We considered that at each sampling occasion, individuals in a population could be detected at 1 of the survey sites or remain undetected and used either multinomial or binomial simultaneous‐count models to estimate abundance, the latter being equivalent to an N‐mixture model with one site. We tested model performance with simulations over a range of detection probabilities, population sizes, growth rates, number of years, sampling occasions, and sites. We then applied our method to 3 critically endangered vulture species in Cambodia to demonstrate the real‐world applicability of the model and to provide the first abundance estimates for these species in Cambodia. Our new approach works best when existing methods are expected to perform poorly (i.e., few sites and large variation in abundance among sites) and if individuals may move among sites between sampling occasions. The approach performed better when there were >8 sampling occasions and net probability of detection was high (>0.5). We believe our approach will be useful in particular for simultaneous surveys at aggregation sites, such as roosts. The method complements existing approaches for estimating abundance of unmarked individuals and is the first method designed specifically for simultaneous counts.

Prostate cancer screening by prostate-specific antigen (PSA); a relevant approach for the small population of the Cayman Islands - Shravana Kumar Jyoti; Camille Blacke; Pallavi Patil; Vibha P. Amblihalli; Amanda Nicholson (Cancer Causes & Control, 2018)

Detection of Tilapia Lake Virus in Egyptian fish farms experiencing high mortalities in 2015 - P Nicholson; M A Fathi; A Fischer; C Mohan; E Schieck; N Mishra; A Heinimann; J Frey; B Wieland; J Jores (Journal of Fish Diseases, 2017)

The eyespot resistance genes Pch1 and Pch2 of wheat are not homoeoloci - M. Pasquariello; J. Ham; C. Burt; J. Jahier; S. Paillard; C. Uauy; P. Nicholson (Theoretical and Applied Genetics, 2017)

Minimally invasive implantable fetal micropacemaker: mechanical testing and technical refinements - Li Zhou; Adriana Nicholson Vest; Raymond A. Peck; Jonathan P. Sredl; Xuechen Huang; Yaniv Bar-Cohen; Michael J. Silka; Jay D. Pruetz; Ramen H. Chmait; Gerald E. Loeb (Medical & Biological Engineering & Computing, 2016)

Pilot Trial of Intravenous Lipid Emulsion Treatment for Severe Nifedipine-Induced Shock - Christine M. Murphy; Cliff Williams; Michael E. Quinn; Brian Nicholson; Thomas Shoe; Michael C. Beuhler; William P. Kerns (Journal of Medical Toxicology, 2016)

A 1.35 Mb DNA fragment is inserted into the DHMN1 locus on chromosome 7q34–q36.2 - Alexander P. Drew; Anthony N. Cutrupi; Megan H. Brewer; Garth A. Nicholson; Marina L. Kennerson (Human Genetics, 2016)

Mapping a Type 1 FHB resistance on chromosome 4AS of Triticum macha and deployment in combination with two Type 2 resistances - C. Burt; A. Steed; N. Gosman; M. Lemmens; N. Bird; R. Ramirez-Gonzalez; S. Holdgate; P. Nicholson (Theoretical and Applied Genetics, 2015)

Evaluation of Skin Fibroblasts from Amyotrophic Lateral Sclerosis Patients for the Rapid Study of Pathological Features - Shu Yang; Katharine Y. Zhang; Ruvini Kariawasam; Monique Bax; Jennifer A. Fifita; Lezanne Ooi; Justin J. Yerbury; Garth A. Nicholson; Ian P. Blair (Neurotoxicity Research, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Morphological and molecular variation in the least madtom Noturus hildebrandi (Siluriformes: Ictaluridae), a Mississippi Embayment endemic: evidence for a cryptic lineage in the Hatchie River - J. J. D. Egge; P. W. Nicholson; A. W. Stark (Journal of Fish Biology, 2015)
Sheared principal component analysis of 40 morphometric characteristics measured for 146 individuals and relative frequencies of pigmentation patterns scored for 980 individuals of the least madtom Noturus hildebrandi , a diminutive catfish endemic to eastern lowland drainages of the Mississippi Embayment region of North America, suggested a clinal pattern of morphological variation extending across the range from north to south. DNA sequence data representing 90 individuals from the mitochondrial gene cytochrome b ( cytb ) analysed using Bayesian phylogenetic methods recovered four major haplotype clades, suggestive of a high degree of isolation by drainage. Individual gene trees of cytb and four additional nuclear loci as well as trees based on concatenated datasets of these genes consistently recovered a cryptic lineage of individuals from the Hatchie River drainage that is morphologically indistinguishable from surrounding populations. Gene‐tree analyses failed to recover a monophyletic N. hildebrandi with respect to Noturus baileyi . A coalescence‐based species tree analysis, however, did recover N. hildebrandi monophyly with high support, suggesting that relationships reflected in individual gene trees and concatenated datasets are in part artefacts of incomplete lineage sorting or an ancient introgressive event. Results are consistent with the hypothesis of an ancient connection between the Hatchie and Tennessee River systems. Current subspecific designations are of limited utility as they reflect morphological variation and are not entirely consistent with phylogeny. Discrepancies between the pattern of variation observed in the morphological and molecular data may be explained by recent local adaptation to individual stream conditions that masks deeper evolutionary divergences.

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Changing patterns of carbon allocation in lake phytoplankton: an FTIR analysis - Andrew P. Dean; James M. Nicholson; David C. Sigee (Hydrobiologia, 2012)

Exploiting co-linearity among grass species to map the Aegilops ventricosa-derived Pch1 eyespot resistance in wheat and establish its relationship to Pch2 - C. Burt; P. Nicholson (Theoretical and Applied Genetics, 2011)

Novel Cell- and Tissue-Based Assays for Detecting Misfolded and Aggregated Protein Accumulation Within Aggresomes and Inclusion Bodies - Dee Shen; Jack Coleman; Eric Chan; Thomas P. Nicholson; Lijun Dai; Paul W. Sheppard; Wayne F. Patton (Cell Biochemistry and Biophysics, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Identification of a QTL conferring seedling and adult plant resistance to eyespot on chromosome 5A of Cappelle Desprez - C. Burt; T. W. Hollins; P. Nicholson (Theoretical and Applied Genetics, 2011)

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

Technical Note: Animal-borne CTD-Satellite Relay Data Loggers for real-time oceanographic data collection - L. Boehme; P. Lovell; M. Biuw; F. Roquet; J. Nicholson; S. E. Thorpe; M. P. Meredith; M. Fedak (Ocean Science, 2009)
The increasing need for continuous monitoring of the world oceans has stimulated the development of a range of autonomous sampling platforms. One novel addition to these approaches is a small, relatively inexpensive data-relaying device that can be deployed on marine mammals to provide vertical oceanographic profiles throughout the upper 2000 m of the water column. When an animal dives, the CTD-Satellite Relay Data Logger (CTD-SRDL) records vertical profiles of temperature, conductivity and pressure. Data are compressed once the animal returns to the surface where it is located by, and relays data to, the Argos satellite system. The technical challenges met in the design of the CTD-SRDL are the maximising of energy efficiency and minimising size, whilst simultaneously maintaining the reliability of an instrument that cannot be recovered and is required to survive its lifetime attached to a marine mammal. The CTD-SRDLs record temperature and salinity with an accuracy of better than 0.005 °C and 0.02 respectively. However, due to the limited availability of reference data, real-time data from remote places are often associated with slightly higher errors. The potential to collect large numbers of profiles cost-effectively makes data collection using CTD-SRDL technology particularly beneficial in regions where traditional oceanographic measurements are scarce or even absent. Depending on the CTD-SRDL configuration, it is possible to sample and transmit hydrographic profiles on a daily basis, providing valuable and often unique information for a real-time ocean observing system.

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)
Summary The marine alphaproteobacterium Roseovarius nubinhibens ISM can produce the gas dimethyl sulfide (DMS) from dimethylsulfoniopropionate (DMSP), a widespread secondary metabolite that occurs in many phytoplankton. Roseovarius possesses a novel gene, termed dddP , which when cloned, confers on Escherichia coli the ability to produce DMS. The DddP polypeptide is in the large family of M24 metallopeptidases and is wholly different from two other enzymes, DddD and DddL, which were previously shown to generate DMS from dimethylsulfoniopropionate. Close homologues of DddP occur in other alphaproteobacteria and more surprisingly, in some Ascomycete fungi. These were the biotechnologically important Aspergillus oryzae and the plant pathogen, Fusarium graminearum . The dddP gene is abundant in the bacterial metagenomic sequences in the Global Ocean Sampling Expedition. Thus, dddP has several novel features and is widely dispersed, both taxonomically and geographically.

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)

Semi-dwarfing Rht-B1 and Rht-D1 loci of wheat differ significantly in their influence on resistance to Fusarium head blight - Srinivasachary; N. Gosman; A. Steed; T. W. Hollins; R. Bayles; P. Jennings; P. Nicholson (Theoretical and Applied Genetics, 2009)

Role of phytohormone signalling in resistance of wheat to Fusarium head blight - P. Nicholson; Sriniv Asachary; N. Gosman; A. Steed; X. Chen (Cereal Research Communications, 2008)

The development of PCR-based markers for the selection of eyespot resistance genes Pch1 and Pch2 - N. H. Chapman; C. Burt; H. Dong; P. Nicholson (Theoretical and Applied Genetics, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Susceptibility to Fusarium head blight is associated with the Rht-D1b semi-dwarfing allele in wheat - Srinivasachary; N. Gosman; A. Steed; J. Simmonds; M. Leverington-Waite; Y. Wang; J. Snape; P. Nicholson (Theoretical and Applied Genetics, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Identification of QTLs for resistance to Fusarium head blight, DON accumulation and associated traits in the winter wheat variety Arina - R. Draeger; N. Gosman; A. Steed; E. Chandler; M. Thomsett; Srinivasachary; J. Schondelmaier; H. Buerstmayr; M. Lemmens; M. Schmolke; A. Mesterhazy; P. Nicholson (Theoretical and Applied Genetics, 2007)

An evaluation of airborne laser scan data for coalmine subsidence mapping - D. R. Palamara; M. Nicholson; P. Flentje; E. Baafi; G. M. Brassington (International Journal of Remote Sensing, 2007)

A novel locus for distal motor neuron degeneration maps to chromosome 7q34-q36 - Sumana Gopinath; Ian P. Blair; Marina L. Kennerson; Jennifer C. Durnall; Garth A. Nicholson (Human Genetics, 2007)

Src kinase promotes adhesion-independent activation of FAK and enhances cellular migration in tamoxifen-resistant breast cancer cells - Stephen Hiscox; Nicola J. Jordan; Liam Morgan; Tim P. Green; Robert I. Nicholson (Clinical & Experimental Metastasis, 2007)

A Method for Extracting RNA from Dormant and Germinating Bacillus subtilis Strain 168 Endospores - R. Moeller; G. Horneck; P. Rettberg; H.-J. Mollenkopf; E. Stackebrandt; W. L. Nicholson (Current Microbiology, 2006)

A new method for conservation planning for the persistence of multiple species - Emily Nicholson; Michael I. Westphal; Karin Frank; Wayne A. Rochester; Robert L. Pressey; David B. Lindenmayer; Hugh P. Possingham (Ecology Letters, 2006)
Although the aim of conservation planning is the persistence of biodiversity, current methods trade‐off ecological realism at a species level in favour of including multiple species and landscape features. For conservation planning to be relevant, the impact of landscape configuration on population processes and the viability of species needs to be considered. We present a novel method for selecting reserve systems that maximize persistence across multiple species, subject to a conservation budget. We use a spatially explicit metapopulation model to estimate extinction risk, a function of the ecology of the species and the amount, quality and configuration of habitat. We compare our new method with more traditional, area‐based reserve selection methods, using a ten‐species case study, and find that the expected loss of species is reduced 20‐fold. Unlike previous methods, we avoid designating arbitrary weightings between reserve size and configuration; rather, our method is based on population processes and is grounded in ecological theory.

Basidiochrome – A Novel Siderophore of the Orchidaceous Mycorrhizal Fungi Ceratobasidium and Rhizoctonia spp. - K. Haselwandter; V. Passler; S. Reiter; D. G. Schmid; G. Nicholson; P. Hentschel; K. Albert; G. Winkelmann (BioMetals, 2006)

Objectives for Multiple‐Species Conservation Planning - EMILY NICHOLSON; HUGH P. POSSINGHAM (Conservation Biology, 2006)
The first step in conservation planning is to identify objectives. Most stated objectives for conservation, such as to maximize biodiversity outcomes, are too vague to be useful within a decision‐making framework. One way to clarify the issue is to define objectives in terms of the risk of extinction for multiple species. Although the assessment of extinction risk for single species is common, few researchers have formulated an objective function that combines the extinction risks of multiple species. We sought to translate the broad goal of maximizing the viability of species into explicit objectives for use in a decision‐theoretic approach to conservation planning. We formulated several objective functions based on extinction risk across many species and illustrated the differences between these objectives with simple examples. Each objective function was the mathematical representation of an approach to conservation and emphasized different levels of threat. Our objectives included minimizing the joint probability of one or more extinctions, minimizing the expected number of extinctions, and minimizing the increase in risk of extinction from the best‐case scenario. With objective functions based on joint probabilities of extinction across species, any correlations in extinction probabilities had to be known or the resultant decisions were potentially misleading. Additive objectives, such as the expected number of extinctions, did not produce the same anomalies. We demonstrated that the choice of objective function is central to the decision‐making process because alternative objective functions can lead to a different ranking of management options. Therefore, decision makers need to think carefully in selecting and defining their conservation goals.

Identification of type I resistance to Fusarium head blight controlled by a major gene located on chromosome 4A of Triticum macha - A. Steed; E. Chandler; M. Thomsett; N. Gosman; S. Faure; P. Nicholson (Theoretical and Applied Genetics, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Analysis of the relationship between parameters of resistance to Fusarium head blight and in vitro tolerance to deoxynivalenol of the winter wheat cultivar WEK0609 - N. Gosman; E. Chandler; M. Thomsett; R. Draeger; P. Nicholson (European Journal of Plant Pathology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Detection and Differentiation of Trichothecene and Enniatin-Producing Fusarium Species on Small-Grain Cereals - P. Nicholson; D.R. Simpson; A.H. Wilson; E. Chandler; M. Thomsett (European Journal of Plant Pathology, 2004)

Variation in Pathogenicity Associated with the Genetic Diversity of Fusarium graminearum - J.P. Carter; H.N. Rezanoor; D. Holden; A.E. Desjardins; R.D. Plattner; P. Nicholson (European Journal of Plant Pathology, 2002)

Development of Stem-base Pathogens on Different Cultivars of Winter Wheat Determined by Quantitative PCR - P. Nicholson; A.S. Turner; S.G. Edwards; G.L. Bateman; L.W. Morgan; D.W. Parry; J. Marshall; M. Nuttall (European Journal of Plant Pathology, 2002)

Exclusion of NFIL3 as the gene causing hereditary sensory neuropathy type I by mutation analysis - Dennis J. Hulme; Ian P. Blair; Jennifer L. Dawkins; Garth A. Nicholson (Human Genetics, 2000)

A study of the impacts of Zn and Cu on two rhizobial species in soils of a long-term field experiment - Amar M. Chaudri; Céline M. G. Allain; Vera L. Barbosa-Jefferson; Fiona A. Nicholson; Brian J. Chambers; Steve P. McGrath (Plant and Soil, 2000)

Exclusion of NFIL3 as the gene causing hereditary sensory neuropathy type I by mutation analysis - Dennis J. Hulme; Ian P. Blair; Jennifer L. Dawkins; Garth A. Nicholson (Human Genetics, 2000)

Detection and Quantification of Individual Fungal Species in Fusarium Disease Complexes of Cereals by Polymerase Chain Reaction (PCR) - P. Nicholson; F. Doohan; H. N. Rezanoor; D. Simpson; P. H. Smith; A. Turner; G. Weston (Cereal Research Communications, 1997)

Interleukin-1α-converting enzyme (ICE) and related cell death genes ICErel-II and ICErel-III map to the same PAC clone at band 11q22.2-22.3 - Jamal Nasir; Jane L. Theilmann; John P. Vaillancourt; Neil A. Munday; Ambereen Ali; Stephen Scherer; Barbara Beatty; Donald W. Nicholson; Michael R. Hayden (Mammalian Genome, 1997)

Localization of the cell death genes CPP32 and Mch-2 to human Chromosome 4q - J. Nasir; J. L. Theilmann; V. Chopra; A. M. Jones; D. Walker; D. M. Rasper; J. P. Vaillancourt; J. E. Hewitt; D. W. Nicholson; M. R. Hayden (Mammalian Genome, 1997)

Studies of the biochemical toxicology of uranyl nitratein the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies of the biochemical toxicology of uranyl nitrate in the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Cephaloridine-induced nephrotoxicity in the Fischer 344 rat: proton NMR spectroscopic studies of urine and plasma in relation to conventional clinical chemical and histopathological assessments of nephronal damage - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1992)

Deformities in chironomid larvae as indicators of pollution (pesticide) stress - C. P. Madden; P. J. Suter; B. C. Nicholson; A. D. Austin (Aquatic Ecology, 1992)

Effects of biliary cannulation and buthionine sulphoximine pretreatment on the nephrotoxicity of para-aminophenol in the Fischer 344 rat - K. P. R. Gartland; C. T. Eason; F. W. Bonner; J. K. Nicholson (Archives of Toxicology, 1990)

Biochemical characterisation of para-aminophenol-induced nephrotoxic lesions in the F344 rat - Kevin P. R. Gartland; Frank W. Bonner; John A. Timbrell; Jeremy K. Nicholson (Archives of Toxicology, 1989)

Enteric inoculation with ERA rabies virus: Evaluation of a candidate wildlife vaccine in laboratory rodents - K. G. Nicholson; Sally P. Bauer (Archives of Virology, 1981)

Interferon response to human diploid cell strain rabies vaccines in man - K. G. Nicholson; E. K. Kuwert; J. Werner; P. Harrison (Archives of Virology, 1979)